Decency - Tore Ellingsen; Erik Mohlin (Lund University, School of Economics and Management, Department of Economics, 2019)
We develop a formal theory of decency. Shared values and understandings give rise to social norms. Norms may mandate collectively optimal behavior, but they need not do so. Furthermore, behavior can be affected by social values even if it stops short of norm compliance. Seeking stronger predictions, we propose a structural model of social values; society endorses efficiency and equality, but condemns ill-gotten gains. The model implies that decent people will tend to avoid situations that encourage prosocial behavior. It also rationalizes the existence of willful ignorance, intention-based negative reciprocity, and betrayal aversion
Keywords: D91; Z13; 330; Culture; Norms; Situations; Social Context; Social Preferences